A regional-based newborn hearing screening program: the Emilia-Romagna model after ten years of legislation - Bianchin, G.; Palma, S.; Polizzi, V.; Kaleci, S.; Stagi, P.; Cappai, M.; Baiocchi, M. P.; Benincasa, P.; Brandolini, C.; Casadio, L.; Di Sarro, S.; Farneti, D.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Hearing loss, occurring in 1-3/1,000 newborns in the well-babies population, is one of the most common congenital diseases, and hearing screening at birth still represents the only means for its early detection. Since 2011 the Emilia Romagna Regional Health Agency has recommended Newborn Hearing Screening for all babies at its birth points and for newborns moving to the region. The aims of this study are to analyze the results of this regional-based Newborn Hearing Screening program and to discuss the impact of the legislative endorsement on the organization. Material and methods. This is an observational retrospective chart study. The recordings of well-babies and babies at Neonatal Intensive Care Units were collected during the period from January 1st 2015 to December 31st 2020. The following data were included: Newborn Hearing Screening coverage, percentage of refer at otoacoustic emissions, prevalence and entity of hearing loss, unilateral/bilateral rate, presence of audiological risk factors. Results. More than 99% of a total of 198,396 newborns underwent the Newborn Hearing Screening test during the period January 1st 2015 to December 31st 2020, with a coverage ranging between 99.6% and 99.9%. Overall, the percentage of confirmed hearing loss cases was about 17-30 % of refer cases, 745 children received a diagnosis of hearing loss (prevalence 3.7/1,000). Considering profound hearing loss cases, these represent 13% of bilateral hearing loss. Conclusions. A regional-based Newborn Hearing Screening program is valuable and cost-effective. In our experience, the centralization of the data system and of the data control is crucial in order to implement its efficiency and effectiveness. Healthcare policies, tracking systems and public awareness are decisive for a successful programme implementation.